1997
DOI: 10.1016/s0092-8674(00)80407-9
|View full text |Cite
|
Sign up to set email alerts
|

GRASP65, a Protein Involved in the Stacking of Golgi Cisternae

Abstract: NEM prevents mitotic reassembly of Golgi cisternae into stacked structures. The major target of NEM is a 65 kDa protein conserved from yeast to mammals. Antibodies to this protein and a recombinant form of it block cisternal stacking in a cell-free system, justifying its designation as a Golgi ReAssembly Stacking Protein (GRASP65). One of the two minor targets of NEM is GM130, previously implicated in the docking of transport vesicles and mitotic fragmentation of the Golgi stack. GRASP65 is complexed with GM13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
489
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(517 citation statements)
references
References 27 publications
21
489
0
3
Order By: Relevance
“…GRASP55-T 222,225 D was also defective in oligomer formation, supporting a model in which the homotypic fusion underlying Golgi ribbon formation depends on membrane cross-bridging by GRASP55 transoligomers. This model for the function of mammalian GRASP proteins largely agrees with previous work on Golgi assembly (Barr et al, 1997;Shorter et al, 1999;Wang et al, 2003Wang et al, , 2005, but its relevance to other described functions for GRASP55 and GRASP65 remains to be determined. GRASP55 binds and may facilitate transport of the transmembrane growth factor ␣ (Kuo et al, 2000), and both GRASP proteins bind members of the p24 protein family, thereby inhibiting p24 recycling to the ER (Barr et al, 2001).…”
Section: Discussionsupporting
confidence: 85%
“…GRASP55-T 222,225 D was also defective in oligomer formation, supporting a model in which the homotypic fusion underlying Golgi ribbon formation depends on membrane cross-bridging by GRASP55 transoligomers. This model for the function of mammalian GRASP proteins largely agrees with previous work on Golgi assembly (Barr et al, 1997;Shorter et al, 1999;Wang et al, 2003Wang et al, , 2005, but its relevance to other described functions for GRASP55 and GRASP65 remains to be determined. GRASP55 binds and may facilitate transport of the transmembrane growth factor ␣ (Kuo et al, 2000), and both GRASP proteins bind members of the p24 protein family, thereby inhibiting p24 recycling to the ER (Barr et al, 2001).…”
Section: Discussionsupporting
confidence: 85%
“…GRASP65 was first described by Barr, Warren and colleagues as a Golgi cisternal stacking factor using an in vitro Golgi reassembly assay. 49 However, RNAi studies have later shown that its main function may not be in cisternal stacking, [50][51][52] but in the formation and/or maintenance of the tubules connecting the stacks within the Golgi ribbon. 52 GRASP65 is a major mitotically-phosphorylated Golgi protein.…”
Section: The Golgi Mitotic Checkpoint Is Regulated By the Golgi Ribbomentioning
confidence: 99%
“…52 GRASP65 is a major mitotically-phosphorylated Golgi protein. [41][42]49 Detailed mapping by mass spectrometry has revealed 4 CDK1-cyclinB phosphorylation sites and two other potential mitotically-regulated phosphorylation sites by nonidentified kinases. 46 All these sites are located at the serine/proline-rich C-terminal portion.…”
Section: The Golgi Mitotic Checkpoint Is Regulated By the Golgi Ribbomentioning
confidence: 99%
“…This observation suggests a mechanism whereby the dispersion of vesicles and tubules into the cytoplasm is prevented. They act as if they were anchored on a template or the "zone of exclusion" (Mollenhauer and Morré, 1978;Rabouille et al, 1995b;Barr et al, 1997). The anchoring of vesicles is thought to be an essential part of the formation of Golgi cisternae.…”
Section: Golgi Stack Biogenesis In Vivomentioning
confidence: 99%
“…Syntaxin 5 was shown to interact with both fusion machineries . p115 (Rabouille et al, 1995a), Golgi matrix 130 (GM130) , GRASP65 (Barr et al, 1997), and GRASP55 were shown to be involved.…”
Section: Introductionmentioning
confidence: 98%